INOVASI PEMANFAATAN TEKNOLOGI INFORMASI DALAM MENINGKATKAN EFISIENSI MANAJEMEN PENDIDIKAN DI MIS 05 DARUSSALAM - Putri, Neni; Permanasari, Revi; Elizah, Tenti; Trinanda, Ririn; Azis, Fadilah; Warsah, Idi; Nurjannah, Nurjannah (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
The utilization of information technology innovation has become a crucial focus in efforts to enhance the efficiency of educational management at MIS 05 Darussalam. The fundamental concept of educational management, particularly educational planning, serves as the cornerstone in achieving optimal educational objectives. This research aims to comprehensively analyze the utilization of information technology innovation in improving educational management efficiency and to identify challenges and obstacles encountered during the implementation of information technology at MIS 05 Darussalam. This research employs a qualitative and descriptive research approach. The data analysis technique categorizes the gathered data based on their respective categories, which will be analyzed through three qualitative data analysis steps, including data reduction, presentation, and conclusion drawing. The results of this research reveal tangible efforts to integrate information technology, especially in administrative aspects such as student data management, schedule arrangement, and attendance recording. However, several challenges, such as budget constraints, insufficient training, and technology accessibility, hinder its implementation. These challenges manifest in the form of classrooms that have not fully utilized technological facilities, encompassing both hardware maintenance and educators' understanding of effectively integrating technology. Overcoming these challenges requires strategic measures, including prudent budget allocation, continuous training, and policy development that supports effective integration. Positive implications include improved management efficiency, transparency, parental involvement, and enriched learning through E-learning.